Effects of sodium chloride on germination and seedling growth of Sunflower (Helianthus annuus L.) - Chowdhury, FM Tonmoy; Halim, MA; Hossain, Feroza; Akhtar, Nahid (Jahangirnagar University Journal of Biological Sciences, 2018)
The response of BARI Sunflower-2 (Helianthus annuus L.) to sodium chloride (NaCl) at germination and early seedling growth was investigated. The seeds and seedlings of sunflower were treated with a series of eight different concentrations of NaCl viz 25, 50, 75, 100, 125, 150, 175 and 200 mM and distilled water (control) and were allowed to grow under plate culture condition. The results showed that the highest salinity concentration (200 mM NaCl) remarkably decreased the germination percentage, germination index and speed of germination of BARI Sunflower-2. Fresh and dry masses of both shoot and root were significantly reduced at a 25-200 mM NaCl solution. Significant reductions of shoot and root length were also noted with the increase of NaCl concentration. The results also illustrate that up to 50 mM NaCl concentration, all of the germination indices and fresh and dry biomass were withstand more than 70%. Thus the present study concluded that the BARI Sunflower-2 could be cultivated in moderately saline soil. Jahangirnagar University J. Biol. Sci. 7(1): 35-44, 2018 (June)